Arthrobacter sp lipase immobilization for preparation of enantiopure masked beta-amino alcohols - Chaubey, Asha; Parshad, Rajinder; Gupta, Pankaj; Taneja, Subhash C.; Qazi, Ghulam N.; Rajan, C. R.; Ponrathnam, S. (Bioorganic & Medicinal Chemistry, 2009)
Recent reports on immobilization of lipase from Arthrobacter sp. (ABL, MTCC 5125; IIIM isolate) on insoluble polymers have shown altered properties including stability and enantioselectivity. Present work demonstrates a facile method for the preparation of enantiopure beta-amino alcohols by modulation of ABL enzyme properties via immobilization on insoluble as well as soluble supports using entrapment/covalent binding techniques. Efficacies of immobilized ABL on insoluble supports prepared from tetraethylorthosilicate/aminopropyltriethoxy silane and soluble supports derived from copolymerization of N-vinyl pyrrolidone-allylglycidyl ether (ANP type)/N-vinyl pyrrolidone-glycidyl methacrylate ( GNP type) for kinetic resolution of masked beta-amino alcohols have been studied vis-a-vis free ABL enzyme/wet cell biomass. The immobilized lipase on different insoluble/soluble supports has shown 21 - 110 mg/g protein binding and 30 - 700 U/g activity for hydrolyzing tributyrin substrate. The findings have shown a significant enhancement in enantioselectivity (ee 99%) vis-a-vis wet cell biomass providing ee 70-90% for resolution of beta-amino alcohols. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Arthrobacter sp lipase; beta-Aminoalcohol; Enantioselectivity; Immobilization; soluble polymer

Immobilization of enantioselective lipase on soluble supports for kinetic resolution of drug intermediates - Chaubey, Asha; Parshad, Rajinder; Taneja, Subhash C.; Deokar, Sarika Babasaheb; Raman, Rajan C.; Ponrathnam, Surendra (Journal of Bioactive and Compatible Polymers, 2012)
The microbial lipase, Arthrobacter sp. lipase (MTCC 5125), from the Indian Institute of Integrative Medicine repository, is known as an effective catalyst for high enantioselective kinetic resolution of drug intermediates. The ABL was immobilized on water-soluble linear supports by covalently binding it to the epoxy groups on the N-vinyl pyrrolidone/allyl glycidyl ether and N-vinyl pyrrolidone/glycidyl methacrylate copolymers. The immobilized lipase, on different soluble supports, had 90-110 mg/g protein binding and 500-700 U/g hydrolysis activities for tributyrin substrate. These copolymers had soluble/insoluble characteristics in different pH ranges, which is an advantage over insoluble copolymers. A soluble polymer at neutral pH provided better accessibility to the immobilized enzyme, which was recovered by precipitation at pH 2-3 for reuse. Kinetic resolution of racemic acyl derivatives of chiral auxiliaries and drug intermediates, namely, phenyl ethanol, aminoalcohol, and fluoxetine intermediate resulted in a significant enhancement in enantioselectivity (99%).
Keywords: Arthrobacter sp lipase; Enantioselectivity; Immobilization; Kinetic resolution; N-vinylpyrrolidone; soluble polymer